Case report-Abdominal cocoon (2001)
Abdominal cocoon is a rare cause of acute intestinal obstruction seen almost exclusively in young adolecent females. Almost all cases are diagosed at surgery and cured by excising the fibrous cocoon. This case although diagnosed accidentally too was treated conservatively successfully.